Comparison study of vertical and horizontal elastic wall on vented square enclosure filled by nanofluid and hexagonal shape with MHD effect - Al-Amir, Qusay Rasheed; Hamzah, Hameed K.; Ali, Farooq H.; Bayraktar, Seyfettin; Arici, Muslum; Hatami, Mohammad (SPRINGER HEIDELBERG, 2022)
In the present paper, numerical investigations of the magnetohydrodynamics forced convection of CNT-water nanofluid inside a square enclosure with one inlet and one outlet were performed. The analysis was carried out for a wide range of Reynolds number (100 <= Re <= 1000), Hartmann number (0 <= Ha <= 60), inclination angle of the magnetic field (0 degrees <= gamma <= 90 degrees), elasticity of the bottom and left walls of the enclosure (10(4) <= E <= 10(7)), location of the center of the hexagonal body in horizontal directions (0.3 <= x(0)/L <= 0.7) and in normal directions (0.25 <= y(0)/L <= 0.75), size of the internal hexagonal body (0.1 <= a/L <= 0.3), and, finally, the volume fraction of the nanoparticles (phi = 0 and 0.1). For the flexible walls of the enclosure, a series of coupled fluid-structure interaction (FSI) analyses were accomplished by utilizing the Arbitrary Lagrangian-Eulerian formulation. It has been revealed that the bottom wall of the enclosure is very sensitive to the elastic wall, while the Nusselt number on the top wall increases with Hartmann number no matter which wall is elastic. It is also the most contributor to the heat transfer at Reynolds numbers of Re = 100 and 500, while the contribution of other walls changes with Reynolds number.
Keywords: CONVECTION HEAT-TRANSFER; FLUID-STRUCTURE INTERACTION; LID-DRIVEN CAVITY; NATURAL-CONVECTION; MIXED CONVECTION; NUMERICAL-SIMULATION; SOLID INTERACTION; WAVY CAVITY; FLOW; GENERATION; Physics